Characterisation Of Opefb Sheets As A Soil Reinforcing Material - Tavana, Mohammadreza Samadi (2011)
Geosynthetics have been one the widely used methods of ground improvement. Environmental awareness and high costs of petroleum-based products stimulated researchers to look for substitutions through the natural products. Various types of natural fibres such as coir, oil palm empty fruit bunches (OPEFB), sisal, jute and etc. are available in hot and humid regions of world. The novelty of utilising natural products could assist the developing countries to reduce the expenses of civil works and ensure the sustainability of their environment.